Russian energy strategy in the European Union, the former Soviet Union region, and China - Sotiriou, Stylianos A. (Lexington Books, 2015)
This book places Eurasia in its entirety within a single explanatory framework and examines, for the first time to that extent, Russia as a Eurasian energy power in its affairs with the two main geopolitical players of the region, the EU and China.